2018
DOI: 10.1507/endocrj.ej18-0107
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue increases shortly after the cessation of GH therapy in adults with Prader-Willi syndrome

Abstract: GH therapy in pediatric patients with Prader-Willi syndrome (PWS) improves body composition, but discontinuation of GH after achieving adult height has been implicated in its deterioration. Although there is evidence for the deleterious effects of visceral adipose tissue (VAT) rather than subcutaneous adipose tissue (SAT) on the development of obesity-related complications, the effects of GH discontinuation on fat distribution in adults with PWS has not been fully investigated. Therefore, we utilized dual-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The beneficial effect of GH on body composition has also been proven indirectly by the observation of impaired body composition after GH treatment was discontinued. Thus, 12 months of discontinuation of GH resulted in a 22% increase in body fat in young adults [12] and to an increase in visceral adipose tissue in adults from 25.2 ± 14.5 to 48.0 ± 26.1 cm 2 (p = 0.024) [13]. In line with these findings, motor skills were impaired 6 months after GH treatment was discontinued [14].…”
supporting
confidence: 53%
“…The beneficial effect of GH on body composition has also been proven indirectly by the observation of impaired body composition after GH treatment was discontinued. Thus, 12 months of discontinuation of GH resulted in a 22% increase in body fat in young adults [12] and to an increase in visceral adipose tissue in adults from 25.2 ± 14.5 to 48.0 ± 26.1 cm 2 (p = 0.024) [13]. In line with these findings, motor skills were impaired 6 months after GH treatment was discontinued [14].…”
supporting
confidence: 53%
“…BMI was included in 16 of the 18 papers discussing body composition. In 2 papers, there was a statistically significant increase in BMI after discontinuation of GH treatment 33,40 . Koizumi et al (2018) looked at the effects of discontinuation of GH treatment on body composition of PWS patients, and determined that BMI increased and LBM decreased as a result of the change 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies 40,41 demonstrated improvements in cholesterol levels, with reduced LDL and increased HDL cholesterol, whilst two other studies did not 32,42 . Two studies reported increased cardiorespiratory exercise capacity 37,38 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is imperative that future studies determine whether the observed effects persist into puberty and adulthood and whether the cessation at this point leads to a deterioration of metabolic parameters and body composition. Koizumi et al reported an increase in LDL and visceral body fat 6 months after cessation of GHT in adults with PWS [ 54 ]. Kuppens et al [ 55 ] also described increases in fat mass when GHT was discontinued in young adults and therefore suggested there were potential benefits in continuing GHT even after adult height is reached.…”
Section: Discussionmentioning
confidence: 99%